VPS13A is closely associated with mitochondria and is required for efficient lysosomal degradation - Sandra Muñoz-Braceras; Alba R. Tornero-Écija; Olivier Vincent; Ricardo Escalante (The Company of Biologists, 2019)
Members of the VPS13 family are associated with various human diseases. In particular, the loss of function of VPS13A leads to chorea-acanthocytosis (ChAc), a rare neurodegenerative disease without available curative treatments. Autophagy has been considered a promising therapeutic target because the absence of VPS13A causes a defective autophagy flux. However, the mechanistic details of this deficiency are unknown. Here, we identified Rab7A as an interactor of one of the VPS13 family members in Dictyostelium discoideum and showed that this interaction is conserved between the human homologs VPS13A and RAB7A in HeLa cells. As RAB7A is a key player in endosome trafficking, we addressed the possible function of VPS13A in endosome dynamics and lysosome degradation. Our results suggest that the decrease in autophagy observed in the absence of VPS13A may be the result of a more general defect in endocytic trafficking and lysosomal degradation. Unexpectedly, we found that VPS13A is closely localized to mitochondria, suggesting that the role of VPS13A in the endolysosomal pathway might be related to inter-organelle communication. We show that VPS13A localizes at the interface between mitochondria-endosomes and mitochondria-endoplasmic reticulum and that the presence of membrane contact sites is altered in the absence of VPS13A. Based on these findings, we propose that therapeutic strategies aimed at modulating the endolysosomal pathway could be beneficial in the treatment of ChAc. This article has an associated First Person interview with the first author of the paper.